Representation and Ideology of Feminism in the Remake of the First Indonesian Heroine Character "Sri Asih" - Setyanto, Daniar Wikan; Rohidi, Tjetjep Rohendi; Haryadi, Toto; Tinarbuko, Sumbo; Yogananti, Auria Farantika; Tari, Eszter (Harmonia: Journal of Arts Research and Education, 2024)
The figure of Sri Asih became a pioneer in the symbolism of women's strength free from the influence of marital status, which was a reaction to the strong patriarchal culture in Indonesia. The figure of Sri Asih was then remade by Studio Bumi Langit and shown in Indonesian cinemas in 2022. The figure of Sri Asih was chosen because she is the first superhero figure from Indonesia. The aspects studied are the elements that form an identity, such as the representation of beauty, characteristics, and the role of women that appear in the figure of Sri Asih. This study uses a descriptive qualitative method and John Fiske's code theory. The urgency of this study is to reveal how the figure of Sri Asih is able to reconstruct the values ​​of women's identity in Indonesian society in the millennial era. The purpose is to explain what codes of reality, representation, and ideology exist in the figure of Sri Asih, and the research study results are the ideas for applying John Fiske's code theory to the figure of Sri Asih. In conclusion, the ideology of feminism in the character of Sri Asih is represented in the form of women's empowerment, gender equality, rejection of violence against women and the collapse of gender stereotypes.